Developing methods to study conformational changes in RNA crystals using a photocaged ligand - Lee, Hyun Kyung; Conrad, Chelsie E.; Magidson, Valentin; Heinz, William F.; Pauly, Gary; Yu, Ping; Ramakrishnan, Saminathan; Stagno, Jason R.; Wang, Yun-Xing (Frontiers in Molecular Biosciences, 2022)
Crystallographic observation of structural changes in real time requires that those changes be uniform both spatially and temporally. A primary challenge with time-resolved ligand-mixing diffraction experiments is asynchrony caused by variable factors, such as efficiency of mixing, rate of diffusion, crystal size, and subsequently, conformational heterogeneity. One method of minimizing such variability is use of a photolabile caged ligand, which can fully saturate the crystal environment (spatially), and whose photoactivation can rapidly (temporally) trigger the reaction in a controlled manner. Our recently published results on a ligand-mixing experiment using time-resolved X-ray crystallography (TRX) with an X-ray free electron laser (XFEL) demonstrated that large conformational changes upon ligand binding resulted in a solid-to-solid phase transition (SSPT), while maintaining Bragg diffraction. Here we investigate this SSPT by polarized video microscopy (PVM) after light-triggered release of a photo-caged adenine (pcADE). In general, the mean transition times and transition widths of the SSPT were less dependent on crystal size than what was observed in previous PVM studies with direct ADE mixing. Instead, the photo-induced transition appears to be heavily influenced by the equilibrium between caged and uncaged ADE due to relatively low sample exposure and uncaging efficiency. Nevertheless, we successfully demonstrate a method for the characterization of phase transitions in RNA crystals that are inducible with a photocaged ligand. The transition data for three crystals of different sizes were then applied to kinetic analysis by fitting to the known four-state model associated with ligand-induced conformational changes, revealing an apparent concentration of uncaged ADE in crystal of 0.43-0.46 mM. These results provide further insight into approaches to study time-resolved ligand-induced conformational changes in crystals, and in particular, highlight the feasibility of triggering phase transitions using a light-inducible system. Developing such approaches may be paramount for the rapidly emerging field of time-resolved crystallography.